Exploring Corporate Social Responsibility in Increasing Gender Diversity in the Banking Sector: Bibliometric Analysis - Fahri, Hamnatul Millah; Kholmi, Masiyah (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Gender diversity in the banking sector is increasingly becoming an important issue, especially in the context of Corporate Social Responsibility (CSR). This study aims to explore the role of CSR in increasing gender diversity in the banking sector and its impact on company performance. The method used is a bibliometric analysis that analyzes publications related to CSR and gender diversity from 2019 to 2024. Data obtained from the Scopus database, with the keyword "Corporate Social Responsibility" resulting in 245 journals, which were then selected into 208 articles. The results of the analysis show a significant increase in the number of publications and citations, indicating a growing research interest in this field. The findings also indicate that companies with higher gender on the board of directors tend to have better levels of CSR engagement and improve corporate reputation. This study underlines the importance of leadership training programs for women and policies that support work-life balance as part of CSR initiatives. The conclusion of this study is that gender integration in CSR strategies can improve overall company performance. A systematic approach to promoting gender equality not only contributes to a positive reputation, but also creates a more inclusive and innovative work environment, which in turn can encourage desire and growth in the banking sector. This study provides insights for stakeholders in developing policies that support gender diversity in the financial industry.